2014
DOI: 10.1177/1077546314532302
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of a partially treated laminated composite magnetorheological fluid sandwich plate

Abstract: In this study, the vibration responses of a partially treated laminated composite magnetorheological (MR) fluid sandwich plate have been investigated. The governing differential equations of motion for a partially treated laminated sandwich plate embedding MR fluid and rubber as the core layer and the laminated composite plate as the face layers are presented in finite element formulation. The validity of the developed finite element formulation is demonstrated by comparing the results in terms of natural freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…For numerical simulation, the material and geometrical properties for partially treated uniform laminated composite MRF sandwich plate (0°/90°/0°/MRF and natural rubber/0°/90°/0°) presented in Ramamoorthy et al. [23] were considered such that: E 1 = 27.83 GPa; E 2 = 9.52 GPa; ν 12 = 0.29; ν 21 = 0.099; G 12 = 2.634 GPa; ρ t = ρ b = 2078 kg/m 3 ; ρ cf = 2812 kg/m 3 ; ρ cr = 910 kg/m 3 ; L = 0.3 m; B = 0.3 m. The thickness of top, bottom and core layers were considered as 1.3 mm, 1.3 mm and 1 mm, respectively. The storage modulus and the loss modulus were G'=-0.05035G2+428.355G+858.8 and G=-0.057G2+452.105G+848.35, respectively.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…For numerical simulation, the material and geometrical properties for partially treated uniform laminated composite MRF sandwich plate (0°/90°/0°/MRF and natural rubber/0°/90°/0°) presented in Ramamoorthy et al. [23] were considered such that: E 1 = 27.83 GPa; E 2 = 9.52 GPa; ν 12 = 0.29; ν 21 = 0.099; G 12 = 2.634 GPa; ρ t = ρ b = 2078 kg/m 3 ; ρ cf = 2812 kg/m 3 ; ρ cr = 910 kg/m 3 ; L = 0.3 m; B = 0.3 m. The thickness of top, bottom and core layers were considered as 1.3 mm, 1.3 mm and 1 mm, respectively. The storage modulus and the loss modulus were G'=-0.05035G2+428.355G+858.8 and G=-0.057G2+452.105G+848.35, respectively.…”
Section: Validationmentioning
confidence: 99%
“…Ramamoorthy et al. [23] presented the numerical simulation on a laminated composite sandwich plate partially treated with MRF and concluded that natural frequencies could be increased with partial treatment of MRF pockets instead of treating MRF fully. Dyniewicz et al.…”
Section: Introductionmentioning
confidence: 99%
“…The governing equations of MR adaptive beam were formulated in the finite element form and also by Ritz method. Ramamoorthy et al [20] investigated vibration responses of a partially treated laminated composite plate integrated with MR fluid segment. The governing differential equations of motion for partially treated laminated plate with MR are presented in finite element formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Vemuluri et al [24] studied the dynamic performance of a tapered sandwich plate partially treated with an MRE layer. e laminated composite plate with an MR fluid was investigated by Ramamoorthy et al [36]. de Souza Eloy et al [22] investigated numerically and experimentally sandwich panels with carbon/epoxy composite skins and a magnetorheological elastomer (MRE) honeycomb core.…”
Section: Introductionmentioning
confidence: 99%